Gastrointestinal symptoms following treatment for anorexia nervosa: A systematic literature review. Issue 6 (2nd February 2021) - West, Madeline; McMaster, Caitlin M.; Staudacher, Heidi M.; Hart, Susan; Jacka, Felice N.; Stewart, Tim; Loughman, Amy; Rocks, Tetyana; Ruusunen, Anu
Abstract: Objective: Gastrointestinal (GI) disturbances are a frequent and burdensome experience for patients with anorexia nervosa (AN). How GI symptoms respond to current interventions is not well characterized, yet is critical to facilitate treatment success, and to inform the development of new treatments for AN. Therefore, the aim of this systematic review was to identify which treatments are effective in improving GI symptoms in patients with AN. Method: A systematic search for studies of AN treatments measuring GI symptoms pre‐ and post‐treatment was conducted in May 2020 (PROSPERO ID: CRD42020181328). After removal of duplicates, title and abstracts of 3, 370 studies were screened. Methodological quality was assessed using National Institute of Health Quality Assessment Tool. Results: Following full‐text screening, 13 studies (12 observational studies and 1 randomized double‐blind placebo‐controlled trial) with 401 participants met eligibility criteria and were included. All observational studies included a component of nutritional rehabilitation, with half ( n  = 6) involving concurrent psychological treatment. The randomized controlled trial reported a drug therapy. Eleven studies reported an improvement in all ( n  = 6) or at least one ( n  = 5) patient‐reported GI symptom following treatment. Two studies reported no change. Methodological quality was fair or poor across all studies. Discussion: This is the first systematic review to synthesize available evidence on the trajectory of patient‐reported GI symptoms from commencement to end of treatment for AN. The results suggest that most studies showed improvement in one or more GI symptom in response to current treatments. Future therapeutic approaches should consider GI symptoms within their design for optimal treatment adherence and outcomes. Resumen: Objetivo: Las alteraciones gastrointestinales (GI) son una experiencia frecuente y gravosa para los pacientes que padecen anorexia nerviosa (AN). La forma en que los síntomas gastrointestinales responden a las intervenciones actuales no está bien caracterizada, sin embargo es fundamental para facilitar el éxito del tratamiento, e informar el desarrollo de nuevos tratamientos para la AN. Por lo tanto, el objetivo de esta revisión sistemática fue identificar qué tratamientos son eficaces para mejorar los síntomas gastrointestinales en pacientes que padecen AN. Método: En mayo de 2020 se llevó a cabo una búsqueda sistemática de estudios de tratamientos para AN que midieron los síntomas gastrointestinales antes y después del tratamiento (PROSPERO ID: CRD42020181328). Después de la eliminación de duplicados, se examinaron el título y los resúmenes de 3370 estudios. La calidad metodológica fue evaluada utilizando la Herramienta de Evaluación de la Calidad del Instituto Nacional de Salud. Resultados: Después de la detección completa de texto, 13 estudios (12 estudios observacionales y un ensayo aleatorizado doble ciego controlado con placebo) con 401 participantes cumplieron con los criterios de elegibilidad y fueron incluidos. Todos los estudios observacionales incluyeron un componente de rehabilitación nutricional, con la mitad (n=6) involucrando un tratamiento psicológico simultáneo. El ensayo controlado aleatorizado reportó tratamiento farmacológico. Once studies informaron de una mejora en todos (n=6) o al menos un (n=5) paciente reportó síntomas gastrointestinales después del tratamiento. Dos estudios no reportaron ningún cambio. La calidad metodológica fue justa o pobre en todos los estudios. Discusión: Esta es la primera revisión sistemática que sintetiza la evidencia disponible sobre la trayectoria de los síntomas GI notificados por el paciente desde el inicio hasta el final del tratamiento para la AN. Los resultados sugieren que la mayoría de los estudios mostraron mejoría en uno o más síntomas gastrointestinales en respuesta a los tratamientos actuales. Los futuros abordajes terapéuticos deben considerar los síntomas gastrointestinales dentro de su diseño para una adherencia y resultados óptimos en el tratamiento.